Perinatal and follow-up outcome study of fetal anomalies with multidisciplinary consultation - Li G; Yang N; Xie M; Xu YJ; Han N; Chen Q; Li H; Wu Y; Cheng CH; Wang Y; Zhou M; Xia B; et al. (Dove Medical Press, 2017)
Genxia Li,1,* Na Yang,2,* Mingkun Xie,1 Yajuan Xu,1 Ning Han,1 Qi Chen,3 Hezhou Li,4 Yueli Wu,5 Chunhua Cheng,1 Yuhong Wang,1 Man Zhou,6 Bo Xia,6 Shuhua Guo,1 Shihong Cui11Department of Obstetrics and Gynecology, The Third Affiliated Hospital of Zhengzhou University, Zhengzhou, 2Department of Obstetrics and Gynecology, The First People’s Hospital in Guangzhou, Guangzhou, 3Department of Pediatric Surgery, 4Department of Ultrasound, 5Department of Genetics Laboratory, The Third Affiliated Hospital of Zhengzhou University, Zhengzhou, China; 6Department of Genetics and Biochemistry, Clemson University, Clemson, SC, USA*These authors contributed equally to this workSynopsis: The establishment of a multidisciplinary consultation system is necessary for the diagnosis of complicated fetal anomalies.Purpose: We aimed to investigate the incidences of different types of fetal anomalies and the influence of multidisciplinary consultation on fetal prognosis.Patients and methods: Multidisciplinary specialists include obstetricians, pediatricians, pediatric surgeons, and experts of ultrasound department and genetic counseling. Consultation was done if the fetal ultrasound examinations showed abnormality. Follow-up, assistance, and guidance for the fetus were achieved by phone calls.Results: Ultrasound screening showed that the incidences of central nervous system anomaly and genitourinary anomaly were 25.80% (275/1,066) and 22.05% (235/1,066), respectively. The detection rates of fetal anomalies were 5.07% (54/1,066), 36.12% (385/1,066), and 58.82% (627/1,066) in pregnant women with gestational age of <20, 20–28, and >28 weeks, respectively. In addition, the fetal cerebral ventriculomegaly accounted for 40.73% of central nervous system malformation, while 71.43% cases with fetal cerebral ventriculomegaly were alleviated during the follow-up period. The proportion of hydronephrosis in genitourinary anomalies was 50.64%, and the remission rate of hydronephrosis was 67.23% during the follow-up period.Conclusion: The establishment of a multidisciplinary consultation system is necessary for the diagnosis of complicated fetal anomalies. The central nervous system anomaly and genitourinary anomaly are the most common fetal anomalies. In addition, the remission rates of cerebral ventriculomegaly and fetal hydronephrosis are high during the follow-up period. Keywords: multidisciplinary consultation, fetal anomalies, pregnancy outcome